Chromosomal alterations and gene pathways of tongue and cheek squamous cell carcinoma / Vincent Chong Vui King. - Chong, Vincent Vui King (2012)
Introduction: Tongue and cheek squamous cell carcinoma (SCC) have different behaviours. In order to understand these behaviours, there is a need to look into the chromosomal alterations and gene pathways that maybe associated with oral cancer at these sites. Therefore, the objective of this study is to determine the chromosomal aberrations and gene pathways involved in tongue and cheek SCC using high resolution array based comparative genomic hybridization (aCGH). Methodology: A genome wide screening with array CGH (SurePrint G3 CGH 1x1M microarray) was performed using gDNA from 20 snap frozen fresh tissues consisting of 12 tongue and 8 cheek SCC (samples from the Malaysian Oral Cancer Database and Tumour Bank System [MOCDTBS] coordinated by OCRCC-UM). Cytosure Software was used to detect the chromosomal aberrations and candidate genes related to the selected regions. Pathway analysis was done using MetaCoreTM software for selected genes. Results: The mean number of chromosomal aberrations per tumour for tongue SCC (22.75±26.58) was higher than cheek SCC (8.63±11.89). The most common amplified regions in tongue SCC were 8q24.22 (33.33%), 8q24.3 (33.33%), 11q13.2 (33.33%), 12q13.13 (33.33%), 14q32.33 (33.33%) and for cheek SCC the most common amplified region was 22q12.3 (25%). For the deleted regions, the most common for tongue SCC were 2q21.1 (16.67%), 6q21 (16.67%) and for cheek SCC were 2q22.1 (25%), 7q35 (25%), 19q13.33 (25%). The most significant pathway involved in tongue SCC was cell adhesion extracellular matrix (ECM) remodelling pathway, while for cheek SCC; it was cadherin-mediated cell adhesion pathway. Conclusion: This study showed that the sites of oral cancer origin have a great influence over the variations in chromosomal aberrations and gene pathways. Nevertheless, the identified chromosomal aberrations genes and their interactive pathways revealed from the present research are worth for further investigations on oral carcinogenesis. (Acknowledgment: Grant of UMRG085/09HTM and PS017/2010A)